Silencing RNA for MMPs May Be Utilized for Cardioprotection - Marta Banaszkiewicz; Anna Krzywonos-Zawadzka; Agnieszka Olejnik; Agnieszka Noszczyk-Nowak; Iwona Bil-Lula (Hindawi-Wiley, 2022)
Ischemia/reperfusion (I/R) injury is accompanied by an increase of matrix metalloproteinase 2 (MMP-2) activity, which degrades heart contractile proteins. The aim of the study was to investigate the effect of MMP-2 small interfering RNA (MMP-2 siRNA) administration on I/R heart. Isolated rat hearts perfused by the Langendorff method were subjected to I/R in the presence or absence of MMP-2 siRNA. The hemodynamic parameters of heart function were monitored. Lactate dehydrogenase (LDH) activity was measured in coronary effluents. Activity and concentration of MMPs in the hearts were measured. Concentration of troponin I (TnI) in coronary effluents was examined as a target for MMP-2 degradation. Recovery of heart mechanical function was reduced after I/R; however, administration of MMP-2 siRNA resulted in restoration of proper mechanical function (p<0.001). LDH activity was decreased after the use of MMP-2 siRNA (p=0.02), providing evidence for reduced cardiac damage. Both MMP-2 and MMP-9 syntheses as well as their activity were inhibited in the I/R hearts after siRNA administration (p<0.05). MMP-2 siRNA administration inhibited TnI release into the coronary effluents (p<0.001). The use of MMP-2 siRNA contributed to the improvement of heart mechanical function and reduction of contractile proteins degradation during I/R; therefore, MMP-2 siRNA may be considered a cardioprotective agent.